Long-term experience with biologic therapies for the treatment of polyarticular juvenile idiopathic arthritis. (May 2013) - Klein, Ariane; Horneff, Gerd
The introduction of biological therapies opened a new era for the treatment of polyarticular juvenile idiopathic arthritis. Remission of disease is now a goal well within reach for many patients. It is now more than a decade since the first biologics for treatment of pediatric rheumatic disease were approved. Long-term effects regarding safety and efficacy are of great interest and these data are now available. This review summarizes published extension studies of biologic therapies, as well as published literature from national biologic registries in juvenile idiopathic arthritis patients. The take-home message of this review is that, especially in the case of etanercept, data show long-lasting efficacy with high adherence rates to the treatment. Tolerability appears to be good over 1-year-long treatment, with no relevant rise in medically relevant infections and yet no obvious association with malignancies. For other biologics, long-term data are relatively scarce.